Anthropogenic Sound Exposure-Induced Stress in Captive Dolphins and Implications for Cetacean Health - Yang, Wei-Cheng; Chen, Chi-Fang; Chuah, Yee-Chien; Zhuang, Chun-Ru; Chen, I-Hua; Mooney, T. Aran; Stott, Jeff; Blanchard, Myra; Jen, I-Fan; Chou, Lien-Siang (Frontiers in Marine Science, 2021)
Many cetaceans are exposed to increasing pressure caused by anthropogenic activities in their marine environment. Anthropogenic sound has been recognized as a possible stressor for cetaceans that may have impacts on health. However, the relationship between stress, hormones, and cytokines secretion in cetaceans is complex and not fully understood. Moreover, the effects of stress are often inconsistent because the character, intensity and duration of the stressors are variable. For a better understanding of how anthropogenic sounds affect the psychophysiology of cetaceans, the present study compared the changes of cortisol concentration and cytokine gene transcriptions in blood samples and behaviors of captive bottlenose dolphins (Tursiops truncatus) after sound exposures. The sound stimuli were 800 Hz pure-tone multiple impulsive sound for 30 min at three different sound levels (estimated mean received SPL: 0, 120, and 140 dB re 1 μPa) that likely cause no permanent and temporary hearing threshold shift in dolphins. Six cytokine genes (IL-2Rα, IL-4, IL-10, IL-12, TNF-α, and IFN-γ) were selected for analysis. Cortisol levels and IL-10 gene transcription increased and IFNγ /IL-10 ratio was lower after a 30-min high-level sound exposure, indicating the sound stimuli used in this study could be a stressor for cetaceans, although only minor behavior changes were observed. This study may shed light on the potential impact of pile driving-like sounds on the endocrine and immune systems in cetaceans and provide imperative information regarding sound exposure for free-ranging cetaceans.